Violência doméstica e justiça : respostas e desafios - Dias, Isabel (2010)
This paper addresses the complex relation between domestic violence and justice. It draws on the analysis of the socially built myths about family and of how they became an obstacle to the intervention of the legal and judicial systems. The paper also provides some analysis about the concept of «syndrome», highlighting its uses in the legal system and describing how the legal system has developed responses to domestic violence in Portugal.